THE EFFECTIVENESS OF ACUPRESSURE THERAPY FOR DYSMENORRHEA IN ADOLESCENT GIRLS - Hidayah, Ardiyanti; Anggraini, Rista Dian; Farida, Siti Nur (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2024)
Background: Dysmenorrhea is pain during menstruation. There are 2 types of dysmenorrhea, namely primary dysmenorrhoea and secondary dysmenorrhoea. Primary dysmenorrhea is dysmenorrhea without any abnormalities in the genital organs. Secondary dysmenorrhea is dysmenorrhea in the presence of abnormalities in the genital organs, such as tumors, inflammation, etc. Acupressure is a development of massage therapy pressing on acupuncture points which increases oxygen saturation and causes muscle relaxation effects. Objectives: This study aims to determine the effectiveness of acupressure therapy for dysmenorrhea pain that occurs in adolescent girls. Design: This research used a one group pretest-posttest design. Methods: This research was conducted in June-October 2020 using primary and secondary data at Patriot Peterongan High School, Jombang Regency. The population of this study was all 60 young women attending Patriot Peterongan High School, Jombang Regency. The sampling technique used in this research was purposive sampling, so that the total research sample was 42 respondents. Data was collected using a pain intensity questionnaire in the form of a numerical VAS (Visual Analog Scale) with an intensity scale (0-10). Acupressure therapy is carried out at the bilateral LI 4 (hegu) and ST 36 pressure points 30 times for 3 consecutive days during menstruation. Data analysis used the Wilcoxon test. Results: The results of the study showed a decrease in the quality of dysmenorrhea pain, namely before therapy, it was 2.67 and SD 0.687. Meanwhile, after acupressure therapy for 3 consecutive days, the average result of dysmenorrhea pain intensity was 1.19 and SD 0.552. The results of the Wilcoxon test showed a decrease in the average intensity of dysmenorrhea pain on day 1, namely 0.22, day 2, namely 0.43 and day 3, namely 0.83 with a P value = 0.00, which means acupressure therapy at point LI 4 ( Hegu) and bilateral ST 36 are effective in reducing dysmenorrhea in adolescent girls. Conclusion: Acupressure therapy at points LI4 and ST 36 is effective in reducing dysmenorrhea in adolescents. As for suggestions for future researchers, this research can be combined with other therapies so that it can be more effective in reducing pain.